Pretrial drug-testing experiments in Milwaukee and Prince George's county - Goldkamp, John S. (Journal of research in crime and delinquency, 1992)
This article describes the results of field experiments involving pretrial drug-testing demonstration projects undertaken in Milwaukee, Wisconsin, and Prince George's County, Maryland, in 1988 and 1989. As part of a six-site effort sponsored by the Bureau of Justice Assistance of the U. S. Department of Justice, the demonstration projects in these two sites sought to implement drug-testing programs at the pre-bail and pretrial release stages of the criminal process to serve as a means for deterring pretrial misconduct i.e., failure to appear in court and rearrest for crimes during pretrial release. The underlying hypotheses of the projects tested by the field experiments were a that pre-bail drug testing would contribute more powerful predictive data that would allow pretrial release decisionmakers better to assess the risks posed by defendants being considered for release over and above the power of other existing information and b that pretrail drug monitoring during pretrial release would deter defendants from crime and flight better than release without drug monitoring. The experimental results reported found no evidence to support either claim. However, the article argues that experimental findings cannot be meaningfully interpreted in isolation from knowledge of the implementation context in the sites. In fact, the demonstration programs in each site experienced challenging obstacles in implementing the programs as envisaged. The need to take into account the difficulties posed by the challenges of implementing new programs in demonstration sites does not, however, undermine the strength of the findings reported. Rather, the implementation difficulties should, in themselves, be seen as important findings concerning the feasibility of such programs. ABSTRACT FROM AUTHOR